1986
DOI: 10.1017/s0022215100100751
|View full text |Cite
|
Sign up to set email alerts
|

Reinke's oedema: a premalignant condition?

Abstract: The purpose of this investigation was to evaluate in the long term the risk of malignancy occurring in the larynx of patients treated for Reinke's oedema. Out of 120 patients treated by surgical stripping of the vocal cords during an eight-year period, 103 comprised the follow-up investigation group. Histological examination of the specimens from the stripping disclosed epithelial microscopic lesions in 26 per cent graded as not more than moderately dysplastic. At the follow-up examination 1 patient had develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…Some investigators speculated that RE may delay or even inhibit malignant transformation, and the relatively low risk of dysplasia is an important factor. Moesgaard Nielsen et al [31] reported 120 patients treated for RE and found 25% patients with mild dysplasia, 75% without dysplasia and 1 case of invasive cancer during the follow-up examination. They proposed that the risk of malignancy may be connected more with smoking than with RE itself.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators speculated that RE may delay or even inhibit malignant transformation, and the relatively low risk of dysplasia is an important factor. Moesgaard Nielsen et al [31] reported 120 patients treated for RE and found 25% patients with mild dysplasia, 75% without dysplasia and 1 case of invasive cancer during the follow-up examination. They proposed that the risk of malignancy may be connected more with smoking than with RE itself.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published study, we presented the histological findings and those from electron scanning and transmission microscopies of Reinke's edema, reporting on different levels of epithelial dysplasia and one case of in situ carcinoma 13 . This concern about possible pre-neoplastic alterations associated with Reinke's edema had already been reported by some authors [14][15] . Marcotullio et al 15 studied 125 cases of Reinke's edema and found 52 cases classified as grade 0 epithelial alterations, 64 grade I, 6 grade II and 3 grade III, among which there was one case of microinvasive carcinoma.…”
Section: Discussionmentioning
confidence: 66%
“…45 This is congruous with other reports in the literature. 20,33,34,40,46 Non-ablative in-office laser management of Reinke's edema was first described using the pulse dye laser, followed by the KTP and more recently by the CO 2 laser. In these methods no immediate size reduction is achieved.…”
Section: Microdebridermentioning
confidence: 99%